Effect of a New Monoclonal Anti-Glycoprotein IX Antibody, KMP-9, on High Shear-Induced Platelet Aggregation - Miyake, Tetsuya; Nomura, Shosaku; Komiyama, Yutaka; Miyazaki, Yasuhiko; Kagawa, Hideo; Masuda, Midori; Takahashi, Hakuo; Fujimura, Yoshihiro; Ikeda, Yasuo; Fukuhara, Shirou (Thrombosis and Haemostasis, 1997)
Human platelet glycoprotein Ib/IX complex acts as a receptor for von Willebrand factor. It is widely accepted that glycoprotein lb is the essential receptor component, but the role of glycoprotein IX is still unclear. We produced a new monoclonal anti-glycoprotein IX antibody (KMP-9) by the hybridoma technique using platelets from a patient with Glanzmann’s thrombasthenia. The epitope of KMP-9 was localized to the C-terminal 8 kD fragment of glycoprotein IX using ELISA analysis of polyethylene-pin-synthesized peptides, as well as Western blot analysis of platelets after digestion with N-glycosidase and Staphylococcus aureus V8 protease. KMP-9 partially inhibited high shear stress-induced platelet aggregation, but had no effect on aggregation induced by ristocetin or low shear stress. Its inhibitory effect on high shear stress-induced aggregation was weaker than that of antiglycoprotein lb or anti-glycoprotein Ilb/IIIa monoclonal antibodies. A 21-mer synthetic peptide (glycoprotein IX L110-G130) inhibited the binding of KMP-9 to platelets. It also competively inhibited the suppression of high shear stress-induced platelet aggregation by KMP-9, but had no direct effect on this aggregation. KMP-9 may be useful to clarify the physiological role of GPIX.